Extended Cost-Benefit Analysis of Maritime Fuel: Comparison of Heavy Fuel Oil and Methanol in Iceland - Rafn Helgason 1990- (2019)
The energy and emissions profile of the maritime industry needs significant adjustments to comply with future maritime regulation. Therefore, alternative fuels have been proposed to meet increasingly higher emission standards, proposed by the International Maritime Organization. Furthermore, the Icelandic government aims to introduce 10% renewable energy into the maritime sector before 2030 as well as eventually phase out heavy fuel oil. This thesis assesses the economic feasibility of introducing methanol into the maritime sector using the method of extended cost-benefit analysis, i.e., adding the economic implications of maritime emissions to the cost side of a cost-benefit analysis. The life-cycle analysis of conventional methanol, renewable methanol and heavy fuel oil are compared and evaluated via dynamic economic evaluation of estimated market prices between 2018 and 2050, as well as the economic implications of the environmental impacts caused by the fuels. Therefore, the purely economic and environmental trade-off between the fuels is shown. Methanol is assessed both in terms of a conventional production pathway but also a pathway that can be considered renewable, i.e., electrolysis and carbon capture and utilization, to assess the prospects of meeting the 10% renewable goal within Iceland’s maritime sector, with methanol. In the purely economic sense, heavy fuel oil is the most feasible option. However, when the economic implications of the environmental impacts are added to the cost of the fuels, conventional methanol becomes cost-competitive in 2018 and becomes the most feasible option in 2050 in three fuel trajectories. Renewable methanol is the most expensive option in all trajectories. Relative cost increase in a transition from HFO to renewable methanol ranges from 215 to 375% of HFO’s total cost in 2018, however, in the most favorable conditions for renewable methanol, in 2050, relative cost increase of said transition goes down to 109,5% of HFO’s total cost, in HFO’s least favorable conditions. ...